SECOND LANGUAGE LEARNERS’ PROJECT ACTIVITY AS A CORE FACTOR BY DEVELOPING SPEAKING SKILLS - Ivanova, Rimma; Ivanov, Andrey; Samozhenov, Sergey (Revista Inclusiones, 2020)
The article offers the work description of the higher education teachers in accordance with their educational strategy for teaching English to students of higher education institutions, who previously had school experience in studying other foreign languages – German or French. The relevance of the proposed work is expressed in the application of the project method on the basis of information technology, that promotes the development of oral communication skills in the most effective way, taking into account the individual characteristics of the student and allows in the future, on the basis of the proposed algorithm of independent work, to conduct a free conversation in a foreign language. The purpose of the article is to show the advantages of intensive teaching methods, involving the use of information technologies, project methodology, creative approach of the teacher, independent activity of students. The described innovative methodology convincingly demonstrates the students’ progress of the oral foreign language speech development from the level of “0” to the level of “B1” during one academic year.